Trends and regional disparities in ischemic heart disease and cerebrovascular disease in Croatia, 1997–2006 - Musić Milanović, Sanja (Array, 2009)
Summary: The aim of this study was to analyze mortality and hospital morbidity from ischemic heart disease (IHD) and cerebrovascular disease (CVD) in the population aged 18+ years in different regions of Croatia, in 1997 to 2006 period. Mortality data were supplied by Central Bureau of Statistics, while hospital morbidity data were obtained from hospital discharge database at Croatian National Institute of Public Health. In Mediterranean region rates of IHD mortality were lower, while rates of hospitalization due to IHD have been higher than those for Croatia in the entire period. Rates of IHD mortality for Continental part have not been different from mean rates for Croatia while rates of hospitalization due to IHD have been lower than rates for Croatia in entire period. Rates of CVD mortality and rates of hospitalization due to CVD for Mediterranean part have been lower than rates for Croatia, while both rates for Continental part have been higher than rates for Croatia during entire period. This analysis identified the regions in which significant deviations from the general trend suggest the need for creation of a new national public health intervention model, focusing on changeable behaviour (lifestyles) risk factors